2015
DOI: 10.7314/apjcp.2015.16.13.5453
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Iranian Cancer Patients Regarding Respecting their Dignity in Hospital Settings

Abstract: Background: There are several factors that threaten the dignity of cancer patients in hospital settings. However, there is limited literature regarding the degree to which dignity of cancer patients is actually respected in daily clinical practice. The aims of this study were therefore to explore cancer patient perceptions of respecting their dignity and related variables in an Iranian cancer specific center. Materials and Methods: This descriptivecorrelational study was carried out among 250 cancer patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(53 citation statements)
references
References 41 publications
1
52
0
Order By: Relevance
“…The Cronbach's alpha coefficient for the PDI-CZ was high (0.92) and provides evidence that this 25-item inventory had very good internal consistency. This result suggests appropriate internal consistency among items, in agreement with other published PDI validation studies (Chochinov et al 7 [0.93]; Ripamonti et al 9 [0.96]; Sautier et al 11 [0.96]; Avestan et al 12 [0.92]; and Rull an et al 13 [0.89]). A reliability coefficient range is considered acceptable between 0.7 and 0.9.…”
Section: Discussionsupporting
confidence: 89%
“…The Cronbach's alpha coefficient for the PDI-CZ was high (0.92) and provides evidence that this 25-item inventory had very good internal consistency. This result suggests appropriate internal consistency among items, in agreement with other published PDI validation studies (Chochinov et al 7 [0.93]; Ripamonti et al 9 [0.96]; Sautier et al 11 [0.96]; Avestan et al 12 [0.92]; and Rull an et al 13 [0.89]). A reliability coefficient range is considered acceptable between 0.7 and 0.9.…”
Section: Discussionsupporting
confidence: 89%
“…The same study showed that age, marital status and time the nurses had worked at the clinic generated a difference in the importance of confidentiality. The findings of Raee et al 9 and Avestan et al 29 revealed that patients’ perception of dignity improved as the patients’ age increased. In a different study, Rassin30 found that new nurses valued human dignity less than senior nurses did.…”
Section: Discussionmentioning
confidence: 94%
“…Cancer patients have many physical, psychological, social and spiritual needs and require high quality nursing care (Yeh et al, 1999;Abdollahzadeh et al, 2014;Abbasnezhad et al, 2015;Avestan et al, 2015;Fathollahzade et al, 2015). Cancer patients are very dependent on their caregivers and the low level of consciousness among nurses may leads to negative many negative consequences in them (Hsiao et al, 2011).…”
Section: Introductionmentioning
confidence: 99%